Characters And Moral Values in “The Lorax” by Chris Renaud - Elis Risa; Gustaman Saragih (Scope : Journal of English Language Teaching, 2022)
The objective of this research is to analyze the character and moral value in “The Lorax” by Chris Renaud. The method employed a descriptive-analysis. Movie script and scenes were the data with tables for characters and moral values to be analyzed as the instruments. The data were analyzed by using Schmidt’s theory for characters and Gulla’s theory for moral values. The research results find out the five types of characters. The protagonist has the most fractions with 26%. Sidekick has the second-highest level at 20%. Another sidekick represents the same 20 % of the total. The antagonist's share of showing in this story is 16 %. The following percentage is 10 % for the mentor and the smallest group in terms of character is a love interest at 8%. The research also results in 11 moral values in this movie.They are kindness 18,7%, commitment 17,6%,  love 14,7%, honesty 12,7%, respect for others 9,8%, integrity 4,9%,  sacrifice 4,9%, compassionate 4,9%, truthfulness 4,9%, tolerance 3,9% and sincerity 3%. Ted Wiggins as the protagonist and the moral value of kindness have the most portion in this movie